Inovasi Buku Cerita Dwi Bahasa Sebagai Upaya Pelestarian Bahasa Daerah dan Meningkatkan Literasi Lingkungan Siswa SD - Yusnia, Yusnia; Heryanto, Debi; Agusdianita, Neza; Azzahra, Fathiya (Jurnal PGSD, 2025)
The preservation of regional languages plays a vital role in maintaining the cultural identity of communities, especially amid rapid globalization. This research addresses the challenge of enhancing environmental literacy among elementary school students through the development of bilingual storybooks focusing on environmental issues, primarily the conservation of endangered species like turtles. The ADDIE model was adopted as the methodological framework for the Research and Development (R&D) study to design, develop, implement, and evaluate these educational materials, which aimed to foster both language retention and environmental consciousness. Validation results indicated high reliability and content validity rates across linguistic, graphic, and material elements, affirming the effectiveness of the storybook in engaging students and enhancing their understanding of environmental conservation. Feedback from teachers and students highlighted the book's practical relevance and appeal, as evidenced by the significant percentage of positive responses regarding its usefulness and educational achievements. Ultimately, this initiative seeks not only to preserve local languages but also to instill a sense of responsibility among students toward environmental stewardship. By integrating cultural and ecological education, the project supports the development of actively engaged and socially responsible learners in a sustainable society.